THE BUSINESS BEHIND THE CHARM OF TOURIST VILLAGES: WHEN THE LAW NEEDS TO BE MORE REAL - Pasaribu, Benhard Kurniawan; Maisyarah (Awang Long Law Review, 2025)
The charm of tourist villages across Indonesia is increasingly attracting attention as an alternative driver of community-based economic growth. Tourist villages serve not only as venues for cultural and natural preservation but also as incubators for various creative economic activities led by local communities. However, behind this economic dynamism, many business practices still operate without clear legal certainty—covering issues such as business entity status, partnership contracts, financial management, and the protection of intellectual property rights. This study explores three key questions: the forms and patterns of business practices within tourist villages, the legal challenges faced by business actors, and the ideal model of business regulation to strengthen the role of rural communities in managing tourist villages. The research employs a juridical-empirical method, using a problem-solving strategy that includes literature review, interviews, and direct observation of two tourist-village sites. The findings show that most business activities in tourist villages are carried out on a micro, small, and medium scale with informally managed operations. Several areas require greater attention and improvement: strengthening synergy between local government and village communities, enhancing legal awareness among local micro-enterprise actors, and addressing tourism safety and insurance standards. The study recommends a business-law regulatory model that formally designates local government as a mandatory partner for mentoring and supervision, implemented under the principle of “Community-Led, Government-Supported,” while ensuring that all major decisions in village tourism management reflect the outcomes of community deliberation.